Comprehensive ecological control of filling station planned activity - Korshunov, Svyatoslav (National Technical University "Kharkiv Polytechnic Institute", 2025)
This study analyses hazardous environmental impact of filling station's planned activity. It needs special attention because of rapid growth of the urban environment, which leads to constant expansions of filling station’s networks to fulfill population's need at fuel. As filling stations are considered as ecological dangerous objects that are necessary to control their activity with environmental impact assessment procedure (EIA). However, EIA procedure concentrates mostly on atmospheric air impact, ignoring impact on water and soils. So, it is proposed to develop informational software for the measures of continuous comprehensive control of filling station activity's ecological impact that can provide more objective assessment of its safety for the environment and population health.
Keywords: filling stations; environmental impact assessment; comprehensive assessment; ecological safety; planned activity